Surface and Catalytic Properties of the γ-Irradiated ZnO-Treated CoO/AlO System - M.M. Doheim; H.A. El-Boohy; M. Mokhtar; G.A. El-Shobaky (Adsorption Science & Technology)
Pure and ZnO-doped Co 3 O 4 /Al 2 O 3 catalysts were subjected to γ-irradiation (0.2–1.6 MGy). These catalysts were employed for the conversion of ethanol and isopropanol at 250–400°C using micropulse techniques. The results obtained showed that ZnO treatment increased the activity and selectivity towards dehydrogenation of the alcohols studied. On the other hand, γ-irradiation resulted in a progressive decrease in activity which fell to a minimum value at 0.8 MGy and then increased back to the original (unirradiated) value on increasing the dose further. γ-Irradiation of ZnO-treated catalysts also led to a decrease in their catalytic activity. However, in this case, the extent of such a decrease as a function of the dose applied decreased as the amount of ZnO in the catalysts increased up to 2.63 wt%. This finding was observed when the catalyzed reaction was conducted at 250–350°C, but the reverse trend was exhibited when the reaction was conducted at 350–400°C.